2006
DOI: 10.1007/s10194-006-0266-6
|View full text |Cite
|
Sign up to set email alerts
|

Value of postmarketing surveillance studies in achieving a complete picture of antimigraine agents: using almotriptan as an example

Abstract: Randomised controlled trials cannot collect all the data relevant for use in everyday clinical practice because drug exposure is limited, endpoints are restricted and some patient populations are excluded. Postmarketing surveillance (PS) studies can add important information for real–world clinical practice. Acute migraine therapy with almotriptan 12.5 mg was evaluated in 4 PS studies, 2 conducted in Spain, 1 in Germany and 1 in France. Almotriptan was associated with a high rate of treatment response and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Randomized controlled trials can provide the highest levels of clinical evidence with the least bias, but cannot collect all data relevant to use in routine clinical practice . Although randomized controlled trials of an extended‐release tablet of sodium valproate in Japanese patients with migraine were not available, this is the first postmarketing surveillance study providing the efficacy and tolerability of valproate for the prophylactic treatment of migraine in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials can provide the highest levels of clinical evidence with the least bias, but cannot collect all data relevant to use in routine clinical practice . Although randomized controlled trials of an extended‐release tablet of sodium valproate in Japanese patients with migraine were not available, this is the first postmarketing surveillance study providing the efficacy and tolerability of valproate for the prophylactic treatment of migraine in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The DDI reports in summaries of product characteristics were likely to be generated from randomized controlled trials and may not be completely representative of the general population. In contrast, a larger and more diverse segment of the general population is involved in postmarketing surveillance studies 22,23. Other contributory factors to the discrepancies are the possibility that both databases might have extrapolated the DDI of one co-prescribed drug to other drugs within the same class, based on different assumptions, and the nonstandardized method of classifying DDIs and assessing their clinical relevance 11…”
Section: Discussionmentioning
confidence: 99%
“…Postmarketing and other studies in a real-world setting provide information on the use of a drug in everyday clinical practice. Postmarketing surveillance studies of ALT conducted in Europe confirmed the results of clinical trials, finding that ALT was associated with a high response rate, that outcomes were improved when treatment was taken when pain was still mild, and that most patients preferred ALT to their previous acute migraine medication [53][54][55][56][57]. The multinational, open-label, observational Standardised Study with ALT in Early Treatment of Migraine (START; n = 454) confirmed that the benefit of early treatment with ALT 12.5 mg (taken within 1 h of onset when pain was still mild) that had been demonstrated in the secondary-care setting in the AwM study was also seen in an everyday general practice setting [58].…”
Section: Post-marketing and Real-world Studiesmentioning
confidence: 73%
“…In the placebocontrolled study in adolescents aged 12-17 years, the most common adverse events with ALT 12.5 mg were somnolence (4.9% vs 1.7% with placebo), dizziness (3.3% vs 1.7%) and nausea ALT (2.7% vs 0%) [69]. Studies in real-world practice support the good tolerability profile of ALT in the treatment of acute migraine, with somnolence, fatigue and nausea amongst the most common adverse events reported [53,58].…”
Section: Tolerabilitymentioning
confidence: 88%